2018
DOI: 10.18203/2320-1770.ijrcog20180180
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, awareness and prevention of cervical cancer among women attending a rural based tertiary care centre, Theni, South India

Abstract: Original Research ArticleKnowledge, awareness and prevention of cervical cancer among women attending a rural based tertiary care centre, Theni, South India Shanthadevi Sambath*, Madhumitha Chandrasekaran INTRODUCTIONCervical cancer is one of the most common cancers worldwide. In India, it is one the leading causes of mortality among women accounting for 23.3% of all cancer deaths. 1 India accounts for about 20% of cervical cancer cases reported from the world. More than threefourth of these patients are diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…16 In present study, only 20.4% ever received counselling about cervical screening which is very similar to findings by Kumar H et al 21 In the present study, only 14.6% ever had a screening test for cervical cancer in their life time. This finding is very similar to that by Nelson SB et al, Sambath S et al, and Elamurugan S et al 16,17,20…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…16 In present study, only 20.4% ever received counselling about cervical screening which is very similar to findings by Kumar H et al 21 In the present study, only 14.6% ever had a screening test for cervical cancer in their life time. This finding is very similar to that by Nelson SB et al, Sambath S et al, and Elamurugan S et al 16,17,20…”
Section: Discussionsupporting
confidence: 91%
“…In present study even though 70.7% had heard cervical cancer only 32.5% were aware of cervical cancer screening which is very similar to findings by Nelson SB et al, in Tamil Nadu (30.9%), Sambath S et al, in Theni (22%) and Dahiya N et al, in New Delhi (23.3%). [16][17][18] In contrast, Aswathy S et al, in Kerala and Elamurugan S et al 19,20 found more than 70% of their participants knew about cervical cancer screening. In the present study only 19.3% had the knowledge of Pap test availability near their locality which was also observed by Kumar H et al, in Mangalore.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This was far better than the 0.5% reported by Bathija et al in Urban slums of Hubli, Karnataka and 0% reported in Theni, Tamil Nadu by Sambath and Chandrasekaran. 14,15 This difference might be explained by the better literacy rate. Both these studies had more than 30% illiterate while our study did not have any illiterates.…”
Section: Discussionmentioning
confidence: 99%
“…This could be probably explained by the differences in the education status, social behavior, media exposure and health facilities available among the study population. [10][11][12][13][14][15][16][17] When asked about cervical cancer screening, only 8.1% were aware of Pap smear test. This was slightly better than the awareness about screening reported (6.5%) by study done in Lucknow.…”
Section: Resultsmentioning
confidence: 99%